Genome-Wide Identification and Characterization of the JAZ Gene Family in Rubber Tree (Hevea brasiliensis) - Chao, Jinquan; Zhao, Yue; Jin, Jie; Wu, Shaohua; Deng, Xiaomin; Chen, Yueyi; Tian, Wei-Min (Frontiers in Genetics, 2019)
Jasmonate ZIM-domain (JAZ) proteins are the master regulators of jasmonate signalling. Jasmonate signalling plays a vital role in the regulation of secondary laticifer differentiation and natural rubber biosynthesis in Hevea brasiliensis. Though several JAZs have been shown to be present in H. brasiliensis latex, the genome-wide screening of HbJAZ members has not yet been explored. In the present study, 18 HbJAZs were identified based on the recent H. brasiliensis genome. Phylogenetic construction revealed that the HbJAZs were clustered into five subgroups and that members within the same subgroup shared highly conserved gene structures and protein motifs. Cis-element analysis of HbJAZ promoters suggested the presence of hormone, stress and development-related cis-elements. HbJAZ1.0, HbJAZ2.0, and HbJAZ5.0 family members interacted with CORONATINE INSENSITIVE1 (COI1) in the presence of coronatine. HbJAZ1.0, HbJAZ2.0, HbJAZ5.0, and HbJAZ12.0 could also interact with each other. Of the 18 HbJAZs, 14 were significantly upregulated upon coronatine treatment. The HbJAZ7.0, HbJAZ8.0d and HbJAZ13.0, were absent from the vascular cambium region. The three genes were also absent from the latex. In the latex, nine of the 14 coronatine-regulated HbJAZs were activated by tapping, while nine HbJAZs were repressed upon ethylene treatment. Among the 15 HbJAZs, the expression patterns of 13 HbJAZs were different between the tapping and ethrel treatments. Based on the computational analyses and gene expression patterns described in this study, we conclude HbJAZ5.0 and HbJAZ10.0b may be key regulators of laticifer differentiation and that HbJAZ8.0b is crucial for regulation of natural rubber biosynthesis in H. brasiliensis.